Role of activation energy in resistance drift of amorphous phase change materials - Wimmer, Martin; Kaes, Matthias; Dellen, Christian; Salinga, Martin (Frontiers in Physics, 2014)
The time evolution of the resistance of amorphous thin films of the phase change materials Ge2Sb2Te5, GeTe and AgIn-Sb2Te is measured during annealing at T = 80°C. The annealing process is interrupted by several fast temperature dips to determine the changing temperature dependence of the resistance. This procedure enables us to identify to what extent the resistance increase over time can be traced back to an increase in activation energy EA or to a rise of the prefactor R*. We observe that, depending on the material, the dominating contribution to the increase in resistance during annealing can be either a change in activation energy (Ge2Sb2Te5) or a change in prefactor (AgIn-Sb2Te). In the case of GeTe, both contribute about equally. We conclude that any phenomenological model for the resistance drift in amorphous phase change materials that is based on the increase of one parameter alone (e.g., the activation energy) cannot claim general validity.